Genome-Wide Association Study Heterogeneous Cohort Homogenization via Subject Weight Knock-Down - Valente, André X. C. N.; Zischkau, Joseph; Shin, Joo Heon; Gao, Yuan; Sarkar, Abhijit (PloS one, 2012)
Population structure can be a source of both false-positive and false-negative findings in a genome-wide association study. This article proposes an approach that helps to reduce the false-positives. It consists of homogenizing the diseased/healthy phenotype ratio across the cohort, by decreasing the statistical weight of selected individuals. After homogenization, the cohort is statistically handled as if originating from a single well-mixed population. The method was applied to homogenize a Parkinson's disease genome-wide association study cohort.